Improved Rendering of Parallax Panoramagrams for a Time-Multiplexed Autostereoscopic Display - Kalai, Adam Tauman; Siegel, Mel (Stereoscopic Displays and Applications IX: Proceedings of SPIE 3295, 1998, 1998)
Parallax-barrier panoramagrams (PPs) can present high-quality autostereoscopic images viewable from different perspectives. The limiting factor in constructing PP computer displays is the display resolution. First, we suggest a new PP display based on time multiplexing in addition to the usual space multiplexing; the barriers move horizontally in front of the display plane. The time multiplexing increases the horizontal resolution. In addition, it permits us to use wider barriers than are acceptable for static displays. We then analyze these displays, showing that wide-barrier PPs have advantages relating to depth-resolution and smoothness, and we present a novel algorithm for rendering the images on a computer.